Parameter optimization and tractive performance evaluation of tracked miner - Wei, Dingbang; Yang, Qiang; Cao, Huade; Xia, Jianxin; Liu, Guangzhi (Marine georesources & geotechnology, 2025)
Enhancing the traction performance of the tracked miner is crucial for ensuring smooth seabed operation. In this study, an experimental device for the interaction between track and deep-sea sediments was designed, aligning with the walking process of the tracked miner. The primary and secondary order of the influence of the driving parameters on the mechanical properties of the undisturbed deep-sea sediments was determined by an orthogonal test, and the pressure-sinkage model and shear stress-displacement model were constructed. Building upon the shear model and the vehicle ground mechanics theory, the driving mechanics model of the tracked miner in the seabed environment was derived, and the track structure and parameter optimization method were proposed. The results show that the experimental factors significantly influence the mechanical properties of undisturbed deep-sea sediments, with the order of influence being grounding pressure > grouser height > shear rate > track shoe length > track shoe width; By optimizing the structural parameters of the "Kunlong 500" tracked miner, the drawbar pull increased by 29.1%, and the sinkage depth reduced by 12.8%. This study quantitatively analyzes the influence of structural parameters in driving performance on the sinkage and shear characteristics of deep-sea sediments, and proposes a new method for optimizing the tractive parameters. It provides new insights for achieving efficient and environmentally friendly movement of tracked miner on the seabed.